Factors associated with positivity for canine visceral leishmaniosis in an endemic area in Brazil - Michelin, Aparecida de Fátima; Maciel, Marilene Oliveira dos Santos; Okajima, Mashami; Nunes, Cáris Maroni [UNESP]; Perri, Sílvia Helena Venturoli [UNESP]; Bonfietti, Lucas Xavier (Elsevier, 2018)
Visceral leishmaniosis (VL) is a public health problem and its occurrence depends primarily on the presence of the vector and susceptible hosts; in the urban environment, the dog is the main reservoir. This study aimed to analyze the distribution of canine visceral leishmaniosis (CVL) and factors associated with it in an urban area endemic for VL. Analysis of the variables was based on 2755 epidemiological records of dogs positive and negative for CVL over a three-year period (2009, 2010 and 2011). A dog was considered positive when it presented amastigotes in the cytological examination of lymph node biopsy and/or was seropositive by immunoenzymatic and indirect immunofluorescence assays. CVL positive dogs were observed throughout the town, but significant differences were observed between the sectors analyzed (P < 0.0001), with two sectors showing higher positivity. CVL prevalence was 35.9% and was significantly associated with age and breed (P < 0.0001). Concerning symptoms, 44.3% of symptomatic dogs were positive for LV (P < 0.0001) in an urban area endemic for this zoonosis.
Keywords: Dogs; Risk factors; Visceral leishmaniosis